1982
DOI: 10.3109/10641968209061641
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Secretion of Acth, Cortisol, and Mineralocorticoids in Cushing's Syndrome

Abstract: The behaviour of plasma levels of ACTH was studied in five untreated patients with pituitary-dependent Cushing's syndrome, with blood samples taken every half an hour for a total period of 24 hours; plasma cortisol, corticosterone, deoxycorticosterone (DOC) and aldosterone were also measured simultaneously. In all cases, above normal secretory impulses of ACTH and cortisol, at approximately the same height, were present throughout the day, while between these peaks the levels were in the normal range. Few peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…- 20 In the present study we also observed that the plasma cortisol level remained high throughout the day with little rhythm in patients with Cushing's syndrome (data not presented). Exogenous glucocorticoid also disturbs the ordinary hypothalamic-pituitary periodicity.…”
supporting
confidence: 62%
“…- 20 In the present study we also observed that the plasma cortisol level remained high throughout the day with little rhythm in patients with Cushing's syndrome (data not presented). Exogenous glucocorticoid also disturbs the ordinary hypothalamic-pituitary periodicity.…”
supporting
confidence: 62%
“…The dissociation of the circadian rhythm of BP from that of HR is consistent with results in Cushing's syndrome 5 and suggests that independent mechanisms regulate HR and BP. The impaired circadian rhythm of Cortisol secretion, which has been demonstrated in certain conditions, 5,23,28 may be important in the observed alteration in the circadian rhythm of BP.…”
Section: Discussionmentioning
confidence: 94%
“…Aldosterone levels ranged from suppressed to high in our patients. It is well known that aldosterone levels may vary greatly in patients with Cushing's disease (Shambelan et al, 1971;Boscaro et al, 1982). A transient intra-adrenal block of the 'late-pathway' of mineralocorticoid production following sustained ACTH stimulation might also play a role (Biglieri et al, 1969; Boscaro et a/., 1982).…”
Section: Discussionmentioning
confidence: 99%